2018
DOI: 10.1242/jeb.163881
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilaas a model to study obesity and metabolic disease

Abstract: Excess adipose fat accumulation, or obesity, is a growing problem worldwide in terms of both the rate of incidence and the severity of obesity-associated metabolic disease. Adipose tissue evolved in animals as a specialized dynamic lipid storage depot: adipose cells synthesize fat (a process called lipogenesis) when energy is plentiful and mobilize stored fat (a process called lipolysis) when energy is needed. When a disruption of lipid homeostasis favors increased fat synthesis and storage with little turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 216 publications
(182 reference statements)
3
135
1
Order By: Relevance
“…However, it is unclear whether this reduction is a metabolic consequence of obesity or an effect of diet. To address this question, we fed Drosophila melanogaster fruit flies an established model of a high sugar diet (Musselman et al, 2011; Musselman and Kühnlein, 2018) and assessed their taste responses to sweet stimuli (see STAR Methods for dietary manipulations). Fruit flies fed a 30% sucrose diet for several weeks develop obesity, metabolic syndrome, peripheral insulin resistance, and recapitulate the hallmarks of kidney and heart disease in their corresponding organs (Musselman et al, 2011; Mussel-man and Kühnlein, 2018; Na et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear whether this reduction is a metabolic consequence of obesity or an effect of diet. To address this question, we fed Drosophila melanogaster fruit flies an established model of a high sugar diet (Musselman et al, 2011; Musselman and Kühnlein, 2018) and assessed their taste responses to sweet stimuli (see STAR Methods for dietary manipulations). Fruit flies fed a 30% sucrose diet for several weeks develop obesity, metabolic syndrome, peripheral insulin resistance, and recapitulate the hallmarks of kidney and heart disease in their corresponding organs (Musselman et al, 2011; Mussel-man and Kühnlein, 2018; Na et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, we fed Drosophila melanogaster fruit flies an established model of a high sugar diet (Musselman et al, 2011; Musselman and Kühnlein, 2018) and assessed their taste responses to sweet stimuli (see STAR Methods for dietary manipulations). Fruit flies fed a 30% sucrose diet for several weeks develop obesity, metabolic syndrome, peripheral insulin resistance, and recapitulate the hallmarks of kidney and heart disease in their corresponding organs (Musselman et al, 2011; Mussel-man and Kühnlein, 2018; Na et al, 2013). In contrast, short, up to 1-week exposures to the high sugar diet (SD; 1.4 calories/gram), lead to fat accumulation compared to animals on a control diet (CD; 0.58 calories/gram), (Figures 1A and S1A), but have no effect on Drosophila insulin-like peptide ( dilp ) transcript levels (Figures S2A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…3 Like humans and rodents, fruit flies exposed to palatable diets rich in sugar or fat overconsume, gain weight, and become at-risk for obesity and metabolic syndrome (Musselman and Kühnlein 2018) . We recently showed that, in addition to promoting feeding by increasing meal size, consumption of high dietary sugar decreased the electrophysiological and calcium responses of the Gr64f+ sweet sensing neurons to sweet stimuli, independently of weight gain (May et al 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…For all dietary manipulations, the following compounds were mixed into standard cornmeal food (Bloomington Food B recipe) (0.58 calories per gram) by melting, mixing, and pouring new vials as in (Musselman and Kühnlein, 2018) and (Na et al, 2013) . For the 30% sugar diet (1.41 calories per gram) Domino granulated sugar w/v was added.…”
Section: Fly Husbandry and Strainsmentioning
confidence: 99%